PERBEDAAN KUALITAS TIDUR SEBELUM DAN SELAMA KEMOTERAPI PADA PASIEN KANKER DI RSUP DR. SARDJITO YOGYAKARTA - , AMINI PURWANTARI, Haryani, S.Kp., M.Kes. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Cancer is a disease that knows no social status. Cancers arise from cells that divide uncontrollably and can result in death. One treatment given chemotherapy. However, chemotherapy has side effects such as fatigue, pain, nausea and vomiting. These side effects affect the patient's quality of sleep. Sleep is an important requirement that must be met adequately is 7-9 hours per day. When cancer occurs in patients with sleep disorders will affect the healing of cancer. Therefore, this study investigated the sleep quality of cancer patients before and during receiving chemotherapy, in order to provide information and an overview of the condition of sleep in order to more cancer patients and accelerate the healing process. Objective: To determine differences in sleep quality of cancer patients before and during chemotherapy in cancer patient in the Instalasi Kanker Tulip RSUP Dr. Sardjito Yogyakarta. Methods: This research was a comparative study with one group pretest posttest design. Data collection using questionnaires Pittsburgh Sleep Quality Index (PSQI) Indonesian version to measure sleep quality of patients.The respondents were 30 peoples.Research time in April-May 2013. Data analysis byMc Nemar test. Results: Mc Nemar test results on the quality of sleep before chemotherapy and during chemotherapy has a value of p = 0.002 (p <0.05) showed that there is a difference between the quality of sleep before and during chemotherapy in cancer patients undergoing outpatient chemotherapy. Conclusion: There is a difference in sleep quality between cancer patients before chemotherapy and during chemotherapy.